KI04 an Aminoglycosides-Derived Molecule Acts as an Inhibitor of Human Connexin46 Hemichannels Expressed in HeLa Cells - Cheng-Wei T. Chang; Naveena Poudyal; Daniel A. Verdugo; Francisca Peña; Jimmy Stehberg; RETAMAL LUCERO, MAURICIO ANTONIO (My University, 2023)
Background: Connexins (Cxs) are proteins that help cells to communicate with the extracellular media and with the cytoplasm of neighboring cells. Despite their importance in several human physiological and pathological conditions, their pharmacology is very poor. In the last decade, some molecules derived from aminoglycosides have been developed as inhibitors of Cxs hemichannels. However, these studies have been performed in E. coli, which is a very simple model. Therefore, our main goal is to test whether these molecules have similar effects in mammalian cells. Methods: We transfected HeLa cells with the human Cx46tGFP and characterized the effect of a kanamycin-derived molecule (KI04) on Cx46 hemichannel activity by time-lapse recordings, changes in phosphorylation by Western blot, localization by epifluorescence, and possible binding sites by molecular dynamics (MD). Results: We observed that kanamycin and KI04 were the most potent inhibitors of Cx46 hemichannels among several aminoglycosides, presenting an IC50 close to 10 μM. The inhibitory effect was not associated with changes in Cx46 electrophoretic mobility or its intracellular localization. Interestingly, 5 mM DTT did not reverse KI04 inhibition, but the KI04 effect completely disappeared after washing out KI04 from the recording media. MD analysis revealed two putative binding sites of KI04 in the Cx46 hemichannel. Results: These results demonstrate that KI04 could be used as a Cx46 inhibitor and could help to develop future selective Cx46 inhibitors.